Viable but not cultivable bacteria - Rita R. Colwell (Uncultivated MicroorganismsUncultivated Microorganisms, 2009)
A well-studied, long-term survival mechanism employed by Gram-positive bacteria is formation of endospores. For Gram-negative bacteria, the assumption has been that a survival state does not exist. However, a dormancy state has been described for Gram-negative bacteria and designated as the viable but nonculturable (VBNC) strategy of nonspore-forming cells. A variety of environmental factors are involved in induction of the viable but nonculturable state and Vibrio cholerae provides a useful paradigm for the VBNC phenomenon. It is now accepted that plate counts cannot be relied upon to enumerate or detect VBNC cells. Therefore, direct methods employing fluorescent staining, molecular genetic probes, and other molecular methods have proven both useful and reliable in detecting and enumerating both culturable and nonculturable cells. A predictive model for cholera has been developed, based on ground truth data gathered using these molecular methods and combining them with data obtained by remote sensing, employing satellites. It is clear that microbiology in the twenty-first century has been enhanced by these new tools and paradigms.